2020
DOI: 10.1039/d0ew00334d
|View full text |Cite
|
Sign up to set email alerts
|

Drinking water microbiology in a water-efficient building: stagnation, seasonality, and physicochemical effects on opportunistic pathogen and total bacteria proliferation

Abstract: The rising trend in water conservation awareness has given rise to the use of water-efficient appliances and fixtures for residential potable water systems. This study characterizes the microbial dynamics at...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
76
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(86 citation statements)
references
References 39 publications
9
76
1
Order By: Relevance
“…Such water quality changes have been related to increased levels of OPs in premise plumbing systems [ 39 , 243 , 244 , 245 ]. In a field sampling study of main water distribution system, 120 water samples were taken throughout a drinking water distribution system.…”
Section: Influence Of Plumbing System Design Configuration and Opmentioning
confidence: 99%
“…Such water quality changes have been related to increased levels of OPs in premise plumbing systems [ 39 , 243 , 244 , 245 ]. In a field sampling study of main water distribution system, 120 water samples were taken throughout a drinking water distribution system.…”
Section: Influence Of Plumbing System Design Configuration and Opmentioning
confidence: 99%
“…These are all critical aspects related to Legionella persistence in man-made systems that contribute to a higher or lower legionellosis risk. The studies considered in Table 1 cover different water settings, including cooling towers [55][56][57], premise plumbing from hospitals [51,52,54,[58][59][60][61][62][63][64] and hotels [45,48,[64][65][66][67][68][69], residential potable water systems [46,70,71], and other facilities [72][73][74][75][76][77][78].…”
Section: Main Research Topicsmentioning
confidence: 99%
“…High Legionella prevalence regardless of the water system [45,46,56,57,63,[67][68][69] Legionella incidence seems to be seasonal dependent [64,69,71,73]…”
Section: Legionella Widespreadmentioning
confidence: 99%
See 1 more Smart Citation
“…and Mycobacterium spp. are several orders of magnitude lower that what has been published in literature (Huang et al, 2021;Isaac and Sherchan, 2020;Ley et al, 2020;Liu et al, 2019) (i.e., 1-10 4 copies mL -1 ). A potential reason for this could be over-chlorination in the systems, which had been reported in the aftermath of HM (Brown et al, 2018), including in early phase of sampling as this study showed.…”
Section: Microbial Communities and Metagenomes Of Pr Samples Were Similar To Those Seen Inmentioning
confidence: 55%